Comparative study of anti-mutated citrullinated vimentin, anti-cyclic citrullinated peptides, and rheumatoid factor predictability in the diagnosis of rheumatoid arthritis - Kumar, Manoj; Chawla, Sumit; Jain, Abhishek (International Journal of Research in Medical Sciences, 2017)
Background: Rheumatoid arthritis (RA) is characterized by synovial joint inflammation, which often leads to progressive joint destruction and disability. Several other auto-antibodies specific to RA have been found .Among them, antibodies against cyclic citrullinated peptides (CCP) are useful for diagnosing RA. Antibodies to mutated citrullinated vimentin (MCV) were described recently in RA. The aim of this study was to determine the diagnostic values of ACCP compared to anti-MCV and Rheumatoid Factor in rheumatoid arthritis patients. Methods: This study included 92 patients with Rheumatoid arthritis (RA) and 35 matching healthy controls. Blood samples were obtained from patients and controls for Erythrocyte Sedimentation Rate (ESR), C Reactive Protein (CRP), Rheumatoid factor (RF). Anti-CCP2 and anti-MCV were determined using ELISA technique. Results: RA group was significantly higher than control group as regard ESR, CRP, RF, Anti-CCP, and Anti- MCV. Conclusion: It was concluded, compared to ACCP, anti-MCV has approximately the same accuracy for the diagnosis of rheumatoid arthritis but higher than Rheumatoid Factor. Level of Evidence: Level II, prospective study, as per guidelines for authors.